ANGPTL4 Expression in Ovarian Granulosa Cells Is Associated With Polycystic Ovary Syndrome - Jiang, Qi; Pan, Ye; Li, Ping; Zheng, Yanjun; Bian, Yuehong; Wang, Wenqi; Wu, Guihua; Song, Tian; Shi, Yuhua (Frontiers in Endocrinology, 2022)
Objectives: To characterize the expression of ANGPTL4 in ovarian granulosa cells (GCs) and its association with polycystic ovary syndrome. Methods: This study included 104 PCOS patients and 112 control women undergoing in vitro fertilization-embryo transfer (IVF-ET) from the reproductive hospital affiliated with Shandong University between 2019 and 2021.The mRNA expression of ANGPTL4 in GCs were assessed by reverse transcription and real-time quantitative (RT-q)PCR, then clinical information for these patients were reviewed and analyzed. Results: The RT-qPCR results showed that ANGPTL4 expression in the control group is significantly lower than that in the PCOS group(P=0.000). It indicated positive association with AMH(r=0.211), HOMA-IR(r=0.174), LDL/HDL(r=0.176), ApoB/ApoAI(r=0.155) and TC/HDL(r=0.189). Additionally, the ANGPTL4 expression in the ovarian granulosa cells might be a independent factor in PCOS(OR:3.345, 95%CI:1.951–5.734) with a close contact with incidence of PCOS (AUC0.704, 95%CI 0.633-0.774,P＜0.001). Conclusions: For the first time our study revealed on the higher ANGPTL4 expression in ovarian GCs with PCOS, and its association with glucose and lipid metabolism showed that ANGPTL4 might play an important role in metabolism and pathogenesis of PCOS.